2002
DOI: 10.1097/00007632-200204150-00025
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Craniocervical Spine Lesion With Osteogenesis Imperfecta

Abstract: For patients with atlantoaxial dislocation, syringomyelia, and basilar impression without clinical symptoms or signs of brain stem compression, occipitocervical spine fusion alone at the reduction of the atlantoaxial dislocation may be indicated because these procedures improve neurologic deficits and prevent postoperative development of basilar impression and enlargement of syringomyelia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…They may have megalocephaly, macroglossia, cranio-vertebral junction problems including atlanto-axial subluxation and short neck contributing to a difficult airway. [45]…”
Section: Discussionmentioning
confidence: 99%
“…They may have megalocephaly, macroglossia, cranio-vertebral junction problems including atlanto-axial subluxation and short neck contributing to a difficult airway. [45]…”
Section: Discussionmentioning
confidence: 99%
“…There is a report of a patient with OI and BI associated with syringomyelia who underwent posterior fusion without posterior fossa decompression and had a good postoperative course [6]. In contrast, Noske et al [7] reported that a patient who underwent Halo traction and achieved improvement in symptoms, and then underwent posterior decompression and fusion, showed improvement for 2 years, but hydrocephalus and other symptoms then worsened and VP shunting was required.…”
Section: Discussionmentioning
confidence: 99%
“…OI has previously been associated with basilar impression (BI) [4,5]. However, OI is relatively rare (1/20,000-30,000) and there are many asymptomatic cases; thus, there are few case reports of surgery for OI and optimal operative procedures have not been defined [5][6][7]. A combination of anterior and posterior surgery with ventriculoperitoneal (VP) shunting has been proposed to be required [5], but it is unclear if such a major operation is needed for all cases of OI with BI.…”
Section: Introductionmentioning
confidence: 99%
“…45,49 With the current rigid cervical spine instrumentation an all posterior occipitocervical spinal fusion and decompression with preoperative HALO traction and/or ventriculoperitoneal shunting has resulted in resolution of neurological symptoms. 44,47,50,51 To reduce risk of nonunion it is the authors’ practice to halt BP treatment for four months postoperatively and use a structural rib grafting to span the instrumentation.…”
Section: Essentials Of the Cervical Spinementioning
confidence: 99%